AB0826 Imaging Modalities for the Classification of Gout: Systematic Literature Review and Meta-Analysis. (10th June 2014) - Ogdie, A.; Taylor, W.; Weatherall, M.; Fransen, J.; Jansen, T.; Neogi, T.; Schumacher, H.R.; Dalbeth, N.
Abstract : Background: Imaging techniques for the classification of gout have advanced significantly since previous classification criteria for gout were established. However, it is not clear whether such imaging techniques should be included in new classification criteria for gout. Objectives: To examine the usefulness of imaging modalities in the classification of gout when compared to monosodium urate (MSU) crystal confirmation as the gold standard in order to inform development of new gout classification criteria. Methods: We systematically reviewed the published literature concerning the diagnostic performance of plain film radiography, magnetic resonance imaging, ultrasound (US), conventional computed tomography, and dual energy computed tomography (DECT). We included only studies using MSU crystal confirmation as the gold standard for case definition of gout. Quality of the studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) tool. Data were pooled and summary test characteristics were calculated when more than one study examined the same imaging feature. Results: Ten studies (7 manuscripts and 3 meeting abstracts) satisfied the inclusion criteria. Six studies examined US, three studies examined DECT and one examined X-ray features of the sternomanubrial joint. All of the studies met most of the quality indicators. All studies occurred in the secondary care setting, with mean gout disease duration of at least 7 years when reported. Three features were examined in more than one study: the double contour sign (DCS) on US, tophus on US, and MSU crystal deposition on DECT. The pooled (95% CI) sensitivity and specificity of US DCS were 0.80 (0.62-0.91) and 0.91 (0.62-0.98) respectively, of US tophus were 0.68 (0.42-0.86) and 0.97 (0.56-0.999) respectively, and of DECT were 0.91 (0.78-0.97) and 0.91 (0.81-0.96) respectively. Conclusions: US and DECT show promise for gout classification but the few studies to date have been in patients with longstanding, established disease. The contribution of imaging over other clinical features for gout classification criteria requires further examination, particularly for those earlier in the course of their disease. Acknowledgements: This study was funded by the American College of Rheumatology and the European Union League Against Rheumatism. We thank Janet Joyce for performing the literature search and Yihui Connie Jiang for administrative support. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1774